Safety and efficacy of robot-assisted percutaneous kyphoplasty under local anesthesia in a day-surgery setting for osteoporotic vertebral compression fractures - Wu, Yaming; Yuan, Yang; Yin, Yi; Gong, Yaqin; Ye, Yaowei; Wu, Li; Qian, Lizhen (Frontiers in Surgery, 2025)
Background and objectivesOsteoporotic vertebral compression fractures (OVCFs) represent a growing healthcare challenge in aging populations. This retrospective study evaluates the safety and efficacy of robot-assisted percutaneous kyphoplasty (PKP) performed under local anesthesia within a day-surgery framework.MethodsClinical data from 127 patients with OVCFs who underwent robot-assisted PKP under local anesthesia in a day-surgery setting at the First People's Hospital of Kunshan between May 2022 and April 2024 were retrospectively analyzed. The cohort comprised 40 males and 87 females, with a mean age of 67.1 ± 6.8 years and a mean body mass index (BMI) of 22.5 ± 3.0 kg/m². The prevalence of comorbidities was as follows: diabetes (n = 36), hypertension (n = 55), coronary heart disease (CHD) (n = 28), and chronic obstructive pulmonary disease (COPD) (n = 15). Data collection included the following parameters: pain intensity (Visual Analog Scale, VAS), Oswestry Disability Index (ODI), operative time, cement volume, complications, length of hospital stay, and hospitalization costs.ResultsAll procedures were successfully completed under local anesthesia with a mean operative time of 56.1 ± 10.2 minutes. The robotic system demonstrated high precision (first-attempt puncture success rate: 95.3%). Significant clinical improvements were observed: VAS scores decreased progressively from 7.9 ± 1.1 to 1.3 ± 0.3 at 6 months [F(4,504) = 386.2, p < 0.001, η² = 0.75], representing an 83.5% improvement, while ODI scores improved by 77.1% [75.2% → 17.2%, F(4,504) = 412.8, p < 0.001, η² = 0.77]. Cobb angle correction reached 5.4° [95%CI:4.1–6.7°, t(126) = 12.6, p < 0.001, d = 1.12]. The complication rate was 4.8% (cement leakage: 2.4%; transient hypotension: 0.8%). Patients were discharged within 34 ± 4.3 h postoperatively, with mean hospitalization costs of 37,100 ± 4,200 RMB. No 30-day readmissions occurred.ConclusionRobot-assisted PKP under local anesthesia in day surgery demonstrates excellent safety and efficacy for OVCF management. This approach combines robotic precision with accelerated recovery pathways, particularly benefiting elderly patients with comorbidities.